2021
DOI: 10.3389/fevo.2021.640210
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation Simplifies Understory Bird Seed-Dispersal Networks in Human-Modified Landscapes

Abstract: Global biodiversity is threatened by land-use changes through human activities. This is mainly due to the conversion of continuous forests into forest fragments surrounded by anthropogenic matrices. In general, sensitive species are lost while species adapted to disturbances succeed in altered environments. However, whether the interactions performed by the persisting species are also modified, and how it scales up to the network level throughout the landscape are virtually unknown in most tropical hotspots of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Thus, reducing the abundance of these families may influence the functioning of different mutualistic processes and may lead to cascading extinctions of various animal groups (Bennett et al, 2009;Kurten, 2013). In fact, Pinto et al (2021) found a reduction in interactions between frugivorous birds and fleshy fruit plants and simplified bird-plant interaction networks in landscapes with small forest amounts in the same biome. Moreover, they assume that the impoverishment of birds and plant communities was responsible for that pattern.…”
Section: Habitat Loss and Changes In Abundance Of Woody Plant Familiesmentioning
confidence: 99%
“…Thus, reducing the abundance of these families may influence the functioning of different mutualistic processes and may lead to cascading extinctions of various animal groups (Bennett et al, 2009;Kurten, 2013). In fact, Pinto et al (2021) found a reduction in interactions between frugivorous birds and fleshy fruit plants and simplified bird-plant interaction networks in landscapes with small forest amounts in the same biome. Moreover, they assume that the impoverishment of birds and plant communities was responsible for that pattern.…”
Section: Habitat Loss and Changes In Abundance Of Woody Plant Familiesmentioning
confidence: 99%
“…Understanding how frugivorous birds are affected by changes in land use is urgently necessary because they comprise the main group of seed dispersers across tropical forests, although they exhibit the greatest extinction rates among birds (Şekercioğlu et al, 2004). Consequently, the loss of frugivores can trigger further extinction cascades (Rogers et al, 2021), disrupting key ecological processes such as seed dispersal (Menezes Pinto et al, 2021; Vidal et al, 2019). Thus, understanding how frugivorous birds respond to land‐use change is crucial to foreseeing ecosystem functioning alteration in human‐modified landscapes.…”
Section: Introductionmentioning
confidence: 99%